(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2019)
يتناول هذا البحث (( جملة الجواب في أسلوب القسم )) دلالةً وتركيباً. فهو يُعنى بها من وجهةٍ تحليليةٍ من جانب وتركيبيةٍ من جانبٍ آخر ، وذلك بتعرّضه للمكوّنات التركيبية لأجزاء الظاهرة اللغوية. يبدأ البحث بتناول تركيب جملة جواب القسم مبيّناً كل ما يطرأ عليها خاصّةً أجزاءها الرئيسة وأحياناً غير الرئيسة ؛ موضّحاً الدلالات المختلفة التي يحدّدها ويؤطّرها السياق الذي تقع فيه هذه الجمل. إذاً فالجملة هي الصورة اللفظية الصغرى للكلام المفيد ؛ في أية لغةٍ من اللغات ، فهي الوسيلة التي يتمّ بها نقل ما يجول في ذهن المتكلّم إلى المتلقّي. فنظام الجملة والكلمة يتباين بتباين الأساليب اللغوية وبما تحتويه تلك الأساليب من دلالات متعدّدة حدّدتها السياقات المختلفة. كل ذلك ليسهل الربط بين الفكرة من جهة والأداء النحوي من جهةٍ أخرى ؛نظراً لأنّ اللغة والفكر شيئان غير منفصلين. This search deals with ((Answer Sentence In Vow Technique)) structurally and Semantically. It adresses the subject from semantic and structural point of view by alluding to the structural component of part of the linguistic phenomenon. This study storts by tackling the structure of vow answer sentence explaining the changes that happen to its main and minor parts as well as its signific cations as determined by its context. In accordance the sentence is then a small verbal image of useful speech in any language. it is a means through which what goes on in the speaker’s mind is communicated to the addresses thus the system of sentence and word varies in accordance with the variation of leguistic styles asx well as with the various significations of those styles as determined by their different context. All this makes the connection easy between the notion on one hand and the syntactical performance on the other hand. taking into consideration that the language and thought are inseparable things.